MEWARTAKAN KRISTUS BERBASIS AUDIO VISUAL - Alphonsus Boedi Prasetijo (Lembaga Penelitian STKIP Widya Yuwana, 2019)
Proclaiming Christ based on Audio Visual is similar with our vocation as a Christian to go to proclaim the Gospel to the world. Pope John Paul II noted in his Message for the 27th Communications Day that the audiocassette and the videocassette are gifts of God, gifts, we may say, kept in His treasury through all the ages until our time, kept — for us. We must clearly understand that he did not give them to us for our harm. Here we know how the Church received the audio visual media as gifts of God. Pierre Babin's idea on symbolic way is recommended for proclaiming of faith. As students in Widya Yuwana Faculty we can improve our skills for a Catholic Religion Education based on Audio Visual Media.